Sericin microparticles enveloped with metal-organic networks as a pulmonary targeting delivery system for intra-tracheally treating metastatic lung cancer - Liu, Jia; Deng, Yan; Fu, Daan; Yuan, Ye; Li, Qilin; Shi, Lin; Wang, Guobin; Wang, Zheng; Wang, Lin (Bioactive materials, 2021)
Chemotherapy is one of the major approaches for the treatment of metastatic lung cancer. However, systemic chemotherapy is limited by poor therapeutic efficiency and severe toxic side effects, due to the extremely low delivery efficacy and non-specificity of anticancer drugs. Herein, we report a sericin microparticles enveloped with metal-organic networks as a pulmonary delivery system for treating lung metastasis of breast cancer in an animal model. The sericin microparticles (SMPs) were prepared using water in oil (w/o) emulsification method. After doxorubicin (DOX) loading, tannic acid (TA)/ferric irons (Fe3+) based metal organic networks (MON) were coated on the particles to obtain DOX-loaded microparticles (DOX@SMPs-MON). The SMPs-MON with good biocompatibility could effectively encapsulate DOX and sustainably unload cargos in a pH-dependent manner. The DOX-loaded microparticles could be uptaken by 4T1 cells, and effectively kill the cancer cells. In vivo, DOX@SMPs-MON was deposited in the lungs and remained for over 5 days after pulmonary administration. In contrast to conventional DOX treatment that did not show significantly inhibitory effects on lung metastatic tumor, DOX@SMPs-MON markedly decreased the number and size of metastatic nodules in lungs, and the lung weight and appearance were similar to those of healthy mice. In summary, the sericin microparticles with MON wrapping might be a promising pulmonary delivery system for treating lung metastatic cancer. [Display omitted] •Biocompatible and biodegradable materials (sericin, tannic acid, ferric iron) based microparticles (SMPs-MON) were developed.•SMPs-MON enhances the doxorubicin accumulation and retention in the lungs as a pulmonary drug release system.•DOX-loaded SMPs-MON could significantly decrease the number and size of metastasis nodules in lungs.